Construction of currency portfolios by means of an optimized investment strategy - Spyros K. Chandrinos; Nikos D. Lagaros (Operations Research Perspectives, 2018)
This work focuses on the development of a technical breakout trading strategy based on the Donchian Channel approach, aiming to the construction of profitable portfolios. In this direction, the Modified Renko Bars (MRBs) were developed first; that proved to be a useful trading tool that responses more accurately than the normal candle sticks to the nature and characteristics of the FOREX market. Subsequently, the parameters of the trading strategy (or system) are calibrated for eight currency pairs, over a period of four years (2006-2009), by comparing the performance of three global search derivative-free optimization algorithms. Then, the returns of the developed system are tested for the next seven years (2010-2016) for each pair and two types of portfolios are constructed; an equal weighted one and a portfolio based on the Kelly criterion. The ultimate objective of this paper is to create currency portfolios based on a novel optimized trading strategy, which could beat constantly the main investors' benchmarks (i.e. S&P500, Barclay CTA Index).
Keywords: 330; Investment strategy; Optimization algorithms; Profitable portfolios; Currencies